Adaptation and validation of the eudaimonic well-being questionnaire to the spanish sport context - Trigueros, Rubén; Pérez-Jiménez, José M.; García-Mas, Alejandro; Aguilar-Parra, José M.; Fernández-Batanero, José M.; Luque de la Rosa, Antonio; Manzano-León, Ana; Navarro-Gómez, Noelia (MDPI, 2021)
Studies to date that have focused on the well-being of the athlete have been based on the hedonic point of view. However, there is a second point of view: eudemonia. Therefore, the present study aims to validate and adapt the Eudemonic Well-Being Scale to the sport context. The study involved 2487 from several sport clubs. Several confirmatory factor analyses were carried out and showed that the six-factor questionnaire was the one with the best fit indices. These results show that the scale is in relation to the original scale (from Spain) and to Waterman’s theoretical model.
Keywords: Deportes - Aspectos psicológicos; Deportistas; Calidad de vida; Sport; Eudemonic; Well-being; Psychometric properties; Confirmatory factorial analysis